Pedagogía de las artes para la construcción de hábitos saludables en niños colombianos con obesidad o pre-diabetes. (2019)
The escenic arts didactic research group leads the intervention proposal. The body as possibility of action in the construction of healthy habits in the frame of the investigation“Effect of the intervention in the lifestyle in the prevention of diabetes type II in Colombian children and teenagers with overweight, obesity or pre-diabetes” formed by researchers from Universidad Antonio Nariño. The purpose of the intervention is to use the escenic arts pedagogy as tool to build healthy body habits and mitigate the risk of having sicknesses derived from sedentary lifestyle and bad food habits; as Colombian children and teenagers are a susceptible population in the development of these diseases, it is pretended to generate a change in their way to act and think through the artistic practice. During each intervention it is pretended to strenght self-steem, self-concept, behaviourism and cognition in the population through drama games, dancing games, sensibilization reflection among others. The intervention is supported in the practice and reflection according to the educative etnographic method and the experiential workshop, from the children and teenagers corporeity in the artistic learning environments, showing them how to make assertive decisions when they work out and eat.This research gives account about the importance of the escenic arts pedagogy to generate changes, specially in the main development stages as childhood and adolescence.